Marine chemistry - Brightwell, Chris (T.F.H. Publications, 2007)
The single most important contributor to success with a marine aquarium is maintaining appropriate water chemistry parameters. However, many hobbyists find the concept of water chemistry to be very daunting. This book starts by addressing basic topics like the definition of "good" water quality and why water quality is so important. It then moves on to more complex subjects, such as how exactly to obtain and maintain good water quality, what fourteen water tests can be performed by the hobbyist, and how to troubleshoot particular water chemistry problems. All of these topics are addressed in great detail, with an emphasis on making the information both clear and comprehensive.